The Correlation Between Islamic Learning Environment and Children's Multiple Intelligence Development - Syafii, Muhammad Hisyam; Rahmatullah, Azam Syukur; Purnomo, Halim; Aladaya, Rudyn (INJIES: Journal of Islamic Education Studies, 2025)
Islamic-based learning environments play a crucial role in developing children's multiple intelligences by integrating Islamic values ​​in physical, social, and spiritual aspects. This study examines the correlation between Islamic learning environments and the development of children's multiple intelligences based on Howard Gardner's theory of multiple intelligences. Using a qualitative approach with a literature review method, this study analyzed various academic sources that discuss Islamic educational environments and their influence on children's cognitive, social, and emotional aspects. The results of the study indicate that Islamic learning environments that emphasize the principles of tauhid, tarbiyah, adab, ta'lim, and fitrah are able to create a conducive atmosphere to optimize various intelligences, including linguistic, logical-mathematical, visual-spatial, musical, kinesthetic, interpersonal, intrapersonal, and naturalistic. Educational approaches such as memorizing the Qur'an, discussion-based learning, and integrating science and Islam have proven effective in increasing children's intelligence potential. In addition, the application of adab in social interactions and the formation of Islamic character contribute to increasing interpersonal and intrapersonal intelligence.In the era of globalization and digitalization, the challenge of maintaining a balance between tradition and modernity is important. Therefore, this study highlights the urgency of utilizing technology that remains in line with Islamic values ​​to enrich the learning experience. The implications of this study provide insight for educators, parents, and policy makers in designing a holistic educational environment, not only academically oriented, but also forming Islamic character and improving children's intelligence as a whole.